ANALYSIS OF THE SEISMIC CONDITION AND CLIMATE CHARACTERISTICS OF THE PARKENT DISTRICT - Mirdavlat , Mirislomov (ANTIS PUBLISHER, 2024)
In the article, the seismic condition of the geographical area where Parkent district is located, the power of earthquakes is analyzed. Also, the climatic features of the park district are thoroughly studied and described. During the article, the results obtained from the research are highlighted with the help of tables.